Knowledge And Practice Of Dental Clinic Students In Preventing The Transmission Of Covid-19 - Rika Cahya Melinia; Ulfa Nurullita; Nur Khamilatusy Sholekhah; Fuad Fatkhurrohman (Odonto : Dental Journal, 2025)
Background: There is a risk of Covid-19 cases occurring between dental practitioners and patients during dental procedures. The inhaled aerosol contains the Covid-19 virus causes dentists, dental nurses or dental clinic students to have a significant risk of transmitting Covid-19. It is important for dental clinic students to have good knowledge and practice in preventing the transmission of Covid-19, especially in dental practice. One of the problems with implementing the prevention of transmission of Covid-19 is the application of standard precautions hand washing which are still often overlooked/ignored. Method: This research is descriptive study with cross sectional approach to describe of the knowledge and practice of dental students in the prevention of Covid-19 transmission in the new normal era at RSGM Unimus. The population was the total of all dental clinic students at RSGM Unimus after deducting the samples that were used as respondents in the validity and reliability test that is 137 people. The sampling technique is simple random sampling with the results of 64 respondents. The variables studied were age, gender, years of practice, knowledge and practice in preventing Covid-19 transmission. Result: As many as 73.4% of respondents had good knowledge and as many as 82.8% of respondents had sufficient practice in preventing the transmission of Covid-19 in the new normal era. Conclusion: Most of the respondents had good knowledge and sufficient practice in preventing the transmission of Covid-19 in the new normal era.